Reversible Dendrite-Free Potassium Plating and Stripping Electrochemistry for Potassium Secondary Batteries - Xiao, Neng; McCulloch, William D; Wu, Yiying (Journal of the American Chemical Society, 2017)
Rechargeable potassium metal batteries have recently emerged as alternative energy storage devices beyond lithium-ion batteries. However, potassium metal anodes suffer from poor reversibility during plating and stripping processes due to their high reactivity and unstable solid electrolyte interphase (SEI). Herein, it is reported for the first time that a potassium bis(fluoroslufonyl)imide (KFSI)-dimethoxyethane (DME) electrolyte forms a uniform SEI on the surface of potassium enabling reversible potassium plating/stripping electrochemistry with high efficiency (∼99%) at ambient temperature. Furthermore, the superconcentrated KFSI-DME electrolyte shows excellent electrochemical stability up to 5 V (vs K/K ) which enables good compatibility with high-voltage cathodes. Full cells with potassium Prussian blue cathodes are demonstrated. Our work contributes toward the understanding of potassium plating/stripping electrochemistry and paves the way for the development of potassium metal battery technologies.